Somatostatin analog (octreotide) and sirolimus immunosuppressive therapy in the treatment of chyloperitoneum and chylothorax in newborns and infants - Gurskaya, A; Sulavko, M; Ekimovskaya, E; Bayazitov, R; Nakovkin, O; Karnuta, I; Klepikova, A; Akhmedova, D; Hagurov, R; Sagoyan, G (Journal of Neonatal Surgery, 2024)
Background: Chyloperitoneum (CP) and chylothorax (CT) are rare conditions that have a high mortality rate and unclear treatment options. Their incidence in neonates ranges from 1 in 20000 to 1 in 187000 live births. This study aims to evaluate the effectiveness of synthetic somatostatin analog (octreotide) and sirolimus therapy in treating chylous pleural and peritoneal collections in newborns and infants. Methods: We conducted a retrospective analysis of 10 children with either chylothorax or chyloperitoneum, treated in our department between 2018 and 2023. The study was approved by the Local Independent Ethics Committee of The National Medical Research Center of Children's Health, under Protocol №7, dated 11 May 2023. The parents voluntarily signed an informed consent form for the off-label use of the drug. We reviewed the medical records for demographic information, clinical presentation, management, and outcome. Results: Our study looked at patients aged between 0 and 5.5 months, with seven cases of chyloperitoneum and three cases of chylothorax. We initially used octreotide, which was then switched to sirolimus if there was no improvement. Octreotide was effective in five children after 10-18 days of treatment, while the effect of sirolimus was observed 8-14 days after starting treatment. One patient, who had a history of a giant omphalocele with primary closure, experienced complications after 8 weeks of sirolimus therapy, including bilateral knee arthritis, leukopenia, and lymphopenia. Fortunately, there were no fatal outcomes. Conclusion: Sirolimus therapy is effective in treating newborns with chylothorax or chyloperitoneum, with a low risk of complications even in those cases not responding to octreotide therapy. It is recommended that octreotide therapy should not exceed 10 days, after which sirolimus can be prescribed.